Deposition of eosinophil cationic protein in vascular lesions in temporal arteritis. Issue 12 (December 1991) - Hällgren, R; Gudbjörnsson, B; Larsson, E; Fredens, K
Abstract : The possible role of the eosinophil and its cytotoxic granule proteins in the vascular lesions seen in temporal arteritis was elucidated. Sixteen sections of biopsy specimens from arteria temporalis showing giant cell arteritis were stained for eosinophil cationic protein (ECP) by polyclonal antibodies and the immunoperoxidase method. Activated eosinophils were identified by monoclonal antibodies linked to alkaline phosphatase. Activated eosinophils and secreted ECP were seen in all layers of the inflamed vessels and were most evident in necrotic lesions and thrombi. Only a small number of granulocytes seen in the adventitia were immunoreactive for cathepsin G, and no extracellular deposits of this neutrophil granule protein were seen. A few immunoreactive eosinophils were found in the adventitia in two of five negative temporal artery biopsy specimens from patients with polymyalgia rheumatica. All eight coronary artery biopsy specimens with atherosclerotic lesions showed no activated eosinophils or secreted ECP. These findings indicate that eosinophils are involved in the vascular lesion in temporal arteritis and suggest that cytotoxic eosinophil granule proteins may contribute to the necrotic lesions and the development of thrombi.